Stationary polaron motion in a polymer chain at high electric fields - Basko, D M; Conwell, E M (Physical review letters, 2002)
We study the stationary motion of a polaron in a conducting polymer in the presence of a high electric field. Using the Su-Schrieffer-Heeger model plus an electric field, we find that at polaron velocities not exceeding the sound velocity, the dissipation of the electronic energy into the lattice occurs via emission of phonons with single selected wave vector. For this case the corresponding contribution to the polaron mobility can be calculated analytically. We discuss the issue of the polaron stability with respect to dissociation in a very high field at supersonic velocities.